Kuns en liturgie – ’n Praktykteoretiese refleksie op die estetika-diskoers - Janse van Rensburg, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Aesthetics and Liturgy – A Practical Theoretical Reflection on the Aesthetics Discourse Against the back drop of a basis theory on esthetics and liturgy, this article applies the principles identified in a previous article to the practical implications within the context of the worship service. Qualitative research tests the use of a painting in a congregational setup. The results of this exercise concur with the indications of the literature study, namely that the use of art in liturgy should be welcomed, but not without the necessary care and theological responsibility.